Media Wacantal dalam Meningkatkan Karakter dan Keterampilan Siswa dalam Pembelajaran Seni Budaya di Sekolah Dasar - Elly Yuliana (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2018)
Digital media as learning resource was rarely used in learning due to teachers’ illiteracy on technology. The research objective was to improve the third-grade children’s character in learning art and culture in Public Elementary School 2 in East Potianak District. This research was designed as a classroom research for improving the children’s character through digital pretty puppets with creative play. The media was developed as playstore application in comical forms. The learning materials contained local folk stories enriched with moral values. The obtained data were analyzed descriptively and qualitatively. Research results show that learning art and culture containing folk stories attract and engage children in learning. The teacher’s skill in exploring folk stories with local values is improved.